Urban Retail in Inland Abruzzo: Between Decline and New Polarities - Bernardo Cardinale; Dante Di Matteo; Concettina Pascetta; Luca Zarrilli (Bollettino della Società Geografica Italiana, 2021)
The multiple geographies of trade in Abruzzo reflect the heterogeneities of regional fabric itself: different constituents like orography, business demography, population density and infrastructure endowment have led to a two-speed growth of the retail sector, where coastal areas have developed faster than inland areas. Through retailers’ and consumers’ prism, this paper offers a focus on the urban retail in some cities of the inland Abruzzo, providing some policy implications. Availing of descriptive and semi-parametric approaches, we found that some public policies, like subsides and pedestrianisation, had an impact on retailers’ perception based in inland areas even higher than those localised in coastal areas, while other features still remain lacking, such as accessibility; besides, compared with coastal areas, consumers’ perceptions in inland areas show an higher social function, where buying behavior is less hedonic and more functional to the needs of local communities.